2011
DOI: 10.1111/j.1600-0870.2010.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble prediction for nowcasting with a convection-permitting model—I: description of the system and the impact of radar-derived surface precipitation rates

Abstract: A B S T R A C TA key strategy to improve the skill of quantitative predictions of precipitation, as well as hazardous weather such as severe thunderstorms and flash floods is to exploit the use of observations of convective activity (e.g. from radar). In this paper, a convection-permitting ensemble prediction system (EPS) aimed at addressing the problems of forecasting localized weather events with relatively short predictability time scale and based on a 1.5 km grid-length version of the Met Office Unified Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…An inflation factor is applied to scale the perturbations. This ensures that the innovation variance is consistent with observations at T + 1 of the forecast (Migliorini et al, 2011;Caron, 2013). A spatially and temporally fixed inflation factor value is used throughout the forecast.…”
Section: Description Of the 15 Km Epsmentioning
confidence: 99%
See 2 more Smart Citations
“…An inflation factor is applied to scale the perturbations. This ensures that the innovation variance is consistent with observations at T + 1 of the forecast (Migliorini et al, 2011;Caron, 2013). A spatially and temporally fixed inflation factor value is used throughout the forecast.…”
Section: Description Of the 15 Km Epsmentioning
confidence: 99%
“…The 1.5 km EPS is described in detail by Migliorini et al (2011). Subsequent improvements to the 1.5 km EPS setup using the so-called scale-selective ETKF to avoid ensemble perturbation mismatches between the ICs and LBCs are described by Caron (2013).…”
Section: Description Of the 15 Km Epsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data-driven modelling of small scale precipitation enhancement patterns in complex topography provides observational support to operational NWP including the convection-permitting models (Migliorini et al, 2011). Radar-based susceptibility maps of orographic precipitation could be used to correct the windward and leeward quantitative precipitation estimation biases present in many NWP models (Bauer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…where ∇z(x) is the gradient vector of elevation evaluated at the (X, Y) spatial coordinates x, u(x,t) is the flow vector with (u,v) components estimated at x at time t. Several algorithms are available to detect precipitation cells from radar imagery (Lakshmanan et al, 2003;Wilson et al, 2004). In this study cells were identified by a simple method that finds the points of maxima of a smoothed precipitation field.…”
Section: Data Preparationmentioning
confidence: 99%